Analysis of equilibrium data of CO2 in aqueous solutions of diethanolamine (DEA), methyldiethanolamine (MDEA) and their mixtures using the modified Kent Eisenberg model - Haji-Sulaiman, M.Z.; Aroua, Mohamed Kheireddine; Benamor, A. (Elsevier, 1998)
Equilibrium data on the absorption of CO2 in aqueous solutions of single and mixed amine was analysed using the Modified Kent Eisenberg model. The experimental value of the examined constant for the formation of carbamate, instead of the fitted value as usual was analysed using the Modified Kent Eisenberg model. The experimental value usually used by other investigators, was applied in the analysis. Data on CO2 loading in aqueous solutions of DEA and MDEA at various temperature (303-323 K) and CO2 partial pressure (0.09-100 kPa) obtained from a stirred reactor was fitted to generate the different parameters in the model. Using these constants, the model was applied to predict the CO2 loading in solutions of DEA and MDEA reported in the literature. Prediction was also made on the loading in solutions of mixed DEA/MDEA obtained from experiments conducted over a range of composition (DEA:MDEA = 0-1) at different temperatures of 303-323 K, as well as those reported in the literature. In all cases, it was found that the model was able to give a relatively good CO2 loading over a wide range of operating conditions both in solutions of single and mixed amine using the constants generated from single amine experiments. It also suggested that the experimental value of the equilibrium constant for the formation of carbamate obtained from an earlier work can be taken as the true value for the reaction.